Unveiling the Aesthetic Charms of 'Khabar Mati': A Deep Dive into Text Folk Performance on the Southern Coastal Shores - Emridawati Emridawati; Awerman Awerman; Irdawati Irdawati; Alfalah Alfalah; Sriyanto Sriyanto (Aksara, 2023)
This research delves into the aesthetic elements of 'Khabar Mati,' a renowned folk theater performance in the Southern Coastal region. The study employs qualitative analysis with a descriptive method to decipher this traditional theatrical expression's intricate artistic and cultural dimensions. The research meticulously examines the narrative and performance aspects of 'Khabar Mati,' providing a comprehensive analysis of the text and its enactment on the stage. Through this in-depth investigation, the study aims to provide valuable insights into the rich aesthetics embedded within 'Khabar Mati.' The findings promise to shed light on the profound artistic heritage of the Southern Coastal communities, offering a deeper understanding of the cultural and aesthetic significance of this captivating folk theater tradition. By scrutinizing the textual and performative aspects, this research provides a holistic exploration of 'Khabar Mati,' contributing to a more comprehensive appreciation of its artistic and cultural merits.